Experts of the streets: The thoughts of experts by experience with a history of crime and substance abuse on working as a team with professionals - Lindström, Janika (European journal of probation, 2021)
Expertise by experience has become increasingly significant in the various fields of social work. This study examines narratives told by experts by experience who have undergone an educational expert-by-experience program for people with a history of crime and substance abuse, with the main focus on the participants’ accounts of their expertise and how it is created when working as a team with a professional. The stories create an image of the expert by experience as an agent who is both an interpreter and an advocate advancing the mutual understanding between the client and the professional as well as someone who promotes the client’s status within the service system. However, the experts’ dual role makes it difficult for them to fully recognize their status and roles in the professional organizations. All in all, the study shows that expertise by experience has much use in social and personal services, including probation.